Assessment Of Labour Concerns And Perceived Effects On Cocoa Farm Operations In Ghana - Agyapong, Dickson; Bakang, John-Eudes Andivi; Osei, Collins Kwabena; Tham-Agyekum, Enoch Kwame; Asiedu, Prince; Ankuyi, Fred; Ntem, Supernatural (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Despite the crucial role of human labour in Ghana's cocoa farming sector, the industry grapples with pressing challenges that threaten its sustainability and productivity. This study considers the intricate dynamics of labour scarcity and rising costs, focusing on the Tafo District, Ghana. We specifically collected data from 100 cocoa farmers who have been farming for over 20 years in the Tafo District using the purposive sampling method, and selected 10 cocoa labourers using a snowball technique. We conducted a descriptive analysis of the data using SPSS and Excel spreadsheet. Labour scarcity, attributed to ‘galamsey' and 'okada’ activities, was acknowledged by 95% of respondents, and 84% noted high labour costs. Farmers pointed out that labour shortages affect the timing and frequency of their farm operations. With labour scarcity attributed to illegal mining and commercial motorcycle transportation, effective government intervention to regulate these activities in agricultural areas will be required.